2014
DOI: 10.1186/1471-2148-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Modern maize varieties going local in the semi-arid zone in Tanzania

Abstract: BackgroundMaize is the most produced crop in Sub-Saharan Africa, but yields are low and climate change is projected to further constrain smallholder production. The current efforts to breed and disseminate new high yielding and climate ready maize varieties are implemented through the formal seed system; the chain of public and private sector activities and institutions that produce and release certified seeds. These efforts are taking place in contexts currently dominated by informal seed systems; local and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
163
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(170 citation statements)
references
References 52 publications
6
163
0
Order By: Relevance
“…In another paper we explore the consequences of this seed management in more depth using single nucleotide polymorphisms to study genetic diversity and differentiation in the local maize seed system in one of the villages in this study [65]. The assessment of households' reasons for cultivating the different genetic resource categories and their perceptions of consumption and production qualities casts more light on the complexity of crop adaptation (Table 3).…”
Section: The Role Of the Seed Systemmentioning
confidence: 99%
“…In another paper we explore the consequences of this seed management in more depth using single nucleotide polymorphisms to study genetic diversity and differentiation in the local maize seed system in one of the villages in this study [65]. The assessment of households' reasons for cultivating the different genetic resource categories and their perceptions of consumption and production qualities casts more light on the complexity of crop adaptation (Table 3).…”
Section: The Role Of the Seed Systemmentioning
confidence: 99%
“…In addition, since 1974 to 2000, maize researchers under maize research program in Tanzania have managed to utilize some potentials from maize germplasm sourced from in and outside the country to release a number of varieties (Kirway et al, 2000). Some of those were able to be adopted because they possessed some traits prefered by the community as well as being connected to the existing farming practices (Westengen et al, 2014). The characteristics of those released varieties extends from plant characteristics, yield performance, disease resistance/ tolerance etc; this gives an indication that maize germplasm present an opportunity for making genetic enhancement against maize production challenges.…”
Section: Importance Of Landracesmentioning
confidence: 99%
“…In most of Africa these informal systems still ensure between 80 and 100% of farmers' seed supply, as highlighted by Louwaars and de Boef (2012). Seed is saved on-farm (recycled), with the aim of reproducing the variety phenotype or adapting a population to the farmer's needs, whether it be maize in Central Mexico, pearl millet in India or organic bread wheat varieties in France (Louette and Smale, 2000;Perales et al, 2003;vom Brocke et al, 2003;Dawson et al, 2012;Westengen et al, 2014). Louette and Smale (2000) showed that farmer phenotype-based selection in traditional maize systems was the key to maintaining the typical ear characteristics of a maize variety under the presence of gene flow.…”
Section: Introductionmentioning
confidence: 96%
“…Farmers' seed selection and management can especially influence the genetic composition of the variety in open-pollinated crops such as pearl millet and maize (Morris et al, 1999;vom Brocke et al, 2003;Warburton et al, 2010;Lakis et al, 2011;Westengen et al, 2014). Using SNP markers, Westengen et al (2014) recently showed that the formal system seed of improved open pollinated maize varieties differentiated significantly from farmer recycled seeds of the same varieties in Tanzania.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation